Superconductivity in pure hafnium kagome electride under high pressure - Pereira, Zenner S.; Cabral, L. [UNESP]; da Silva, E. Z. (American Physical Society (APS), 2025)
Superconductivity in pure ω-Hf under high pressures (40−60GPa) was investigated using density functional theory (DFT) combined with the Migdal-Eliashberg theory. The results indicate that interstitial anionic electrons (IAE) in pure ω-Hf exhibit both kagome and hexagonal electride structures, with interstitial electrons distributed across two distinct crystal planes. The results also show that spin-orbit coupling significantly modifies the conduction electronic band-structure, inducing a Van-Hove singularity at the Fermi level, which enhances the superconducting critical temperature (Tc) from approximately 3.0K to 5.3K at 60GPa. In addition, interstitial electrons in the valence band at the Fermi level also contribute to superconductivity. These Tc values agree well with previously reported experimental results. Furthermore, we demonstrate that crystal planes hosting anionic interstitial electrons exhibit anisotropy and low work function of 3.01eV along the [001] direction, consistent with the characteristics of electride materials.